THE EFFECT OF WARM COMPRESS ON THE INTENSITY OF LABOR PAIN IN THE ACTIVE PHASE OF THE FIRST STAGE IN THE PRATAMA CLINIC AFISYA PERCUT SEI TUAN DISTRICT IN 2025 - Situmorang, Khairunnisa; Lasmini; Humaida Hanim; Mesrida Simarmata; Siska Suci Triana Ginting; Nia Habelahan (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Pain in thel activel phasel of first stagel of labor is a physiological elxpelrielncel that can causel discomfort and anxielty in laboring mothelrs. Non-pharmacological pain managelmelnt such as warm comprelssels is bellielveld to bel elffelctivel in relducing pain intelnsity with minimal risk. This study aims to analyzel thel elffelct of warm comprelssels on thel intelnsity of pain in thel activel phasel of first stagel of labor at thel Villagel Helalth Post (Poskelsdels) in Pelnanggoan Dureln Villagel, Palelmbang City. Thel study useld a quasi-elxpelrimelntal delsign with a onel-group preltelst-posttelst delsign. Thel study samplel was 30 mothelrs in thel activel phasel of first stagel labor who welrel divideld into trelatmelnt groups (n=15) and control groups (n=15) with a total sampling telchniquel. Pain was melasureld using thel Numelric Rating Scalel (NRS) belforel and aftelr thel intelrvelntion. Data analysis was pelrformeld using a paireld t-telst. Thel relsults showeld a delcrelasel in thel pain scalel in thel trelatmelnt group from an avelragel of 3.93 to 3.53, with p=0.011 (p<0.05), which melans thelrel is a significant elffelct of warm comprelssels on relducing thel intelnsity of pain in thel activel phasel of first stagel of labor. Conclusion: Warm comprelssels can bel useld as an elffelctivel non-pharmacological intelrvelntion to relducel pain in thel activel phasel of first stagel of labor.